Haplotype analysis of SERPINE1 gene: Risk for aneurysmal subarachnoid hemorrhage and clinical outcomes - Lin, Mingkuan (Mol Genet Genomic Med, 2019)
BACKGROUND: Aneurysmal subarachnoid hemorrhage (aSAH) has high fatality and permanent disability rates due to the severe damage to brain cells and inflammation. The SERPINE1 gene that encodes PAI‐1 for the regulation of tissue plasminogen activator is considered an important therapeutic target for aSAH. METHODS: Six SNPs in the SERPINE1 gene (in order of rs2227631, rs1799889, rs6092, rs6090, rs2227684, rs7242) were investigated. Blood samples were genotyped with Taqman genotyping assays and pyrosequencing. The experiment‐wide statistically significant threshold for single marker analysis was set at p < 0.01 after evaluation of independent markers. Haplotype analysis was performed in Haplo.stats package with permutation tests. Bonferroni correction for multiple comparison in dominant, additive, and recessive model was applied. RESULTS: A total of 146 aSAH patients and 49 control subjects were involved in this study. The rs2227631 G allele is significant (p = 0.01) for aSAH compared to control. In aSAH group, haplotype analysis showed that G5GGGT homozygotes in recessive model were associated with delayed cerebral ischemia (p < 0.01, Odds Ratio = 5.14, 95% CI = 1.45–18.18), clinical vasospasm (p = 0.01, Odds Ratio = 4.58, 95% CI = 1.30–16.13), and longer intensive care unit stay (p = 0.01). By contrast, the G5GGAG carriers were associated with less incidence of cerebral edema (p < 0.01) and higher Glasgow Coma Scale (p < 0.01). The A4GGGT carriers were associated with less incidence of severe hypertension (>140/90) (p < 0.01). CONCLUSION: The results suggested an important regulatory role of the SERPINE1 gene polymorphism in clinical outcomes of aSAH.